Воспоминания о С. А. Плетнёвой (с предисловием В. С. Флёрова) - Эрдели, И. (Хазарский альманах, 2016)
Известный венгерский археолог Иштван Эрдели вспоминает, как он и группа венгерских археологов участвовали в раскопках Маяцкого городища в 1975, 1977–1982 гг. В центре внимания автора – его сложные отношения с С. А. Плетнёвой. Автор также рассказывает о своих представлениях тех лет об истории авар, алан, болгар, венгров. В предисловии В.С. Флёров дополняет рассказ И. Эрдели собственными воспоминаниями. The well-known Hungarian archeologist Ishtvan Erdeli remembers as he in composition the group of the Hungarian scientists participated in excavations of the Mayatsky site in 1975, 1977–1982. In a spotlight are his difficult relations with a famous Russian archeologist S.A. Pletnyova. The author similarly tells about his ideas of those years about history of the Avars, Alans, Bulgarians and Hungarians. In his foreword V. S. Flyorov complements Ishtvan Erdeli's story with own remembrances.